Treasure Hunt: Ethical Egoism vs Individual Anarchism - Immanuel Wijaya (Institute of Research and Community Outreach - Petra Christian University, 2020)
This creative project is a novel with an urban-fantasy as the setting and adventure fiction as the plot framework. This novel is depicting a team of a treasure hunters, Michael Harmanto and Lucius Ferdinan. The two of them are trying to find the lost treasures of Kahja, in which they will be asked and tested in their perseverance and ego. In this creative work, I use Egoism as my topic, and I chose on understanding how egoism if applied ethically, can be treated as a good thing as my theme. Through this, I can show the process and the struggle of people clashing and betraying each other in the name of the egoistic desire of reaching their own personal goal. This story, topic, and theme were inspired by how it would be contrasting to the Indonesian philosophy as a nation. The main viewpoints which are ethical egoism and egoistical anarchism will be depicted in the way the two main characters Michael and Lucius’ attitudes, methods, and results. Keywords: ethical egoism, egoistic anarchism, urban-fantasy, adventure